Becker muscular dystrophy associated with sarcomeric hypertrophic cardiomyopathy in a paediatric patient: a case report. Issue 3 (13th July 2019) - Dolader, Paola; Field, Ella; Sarkozy, Anna; Kaski, Juan Pablo
Abstract: Background : Becker muscular dystrophy (BMD) is a neuromuscular disorder associated with myocardial involvement. The most frequent presentation is dilated cardiomyopathy. There have been isolated reports of hypertrophic cardiomyopathy (HCM) in association with BMD, but it is unclear whether these patients had an additional aetiology. Case summary : A 10-year-old boy was diagnosed with BMD having presented with a history of muscular pain during exercise and elevated serum creatine kinase levels. A cardiac screening was arranged and the echocardiogram confirmed an asymmetric septal hypertrophy. Given the unusual finding of HCM in this patient with BMD, we performed genetic testing for HCM-causing mutations and identified a likely pathogenic variant in heterozygosis in the beta-myosin heavy chain gene. Discussion : This case highlights the importance of considering additional aetiologies of cardiac disease in the presence of infrequent phenotypic expressions in neuromuscular disorders.